PENANGANAN KASUS PENAMBANGAN GALIAN C ILEGAL DI KAWASAN PEGUNUNGAN KENDENG SELATAN DAN PEGUNUNGAN KENDENG UTARA DI KABUPATEN PATI - Dwiyana Achmad Hartanto; Suyoto - (Universitas Muhammadiyah Semarang, 2017)
ati regency is one of the regencies that has several areas and landscapes in the form of limestone mountains, covering the South Kendeng Mountains and the North Kendeng Mountains. Such landscape is an area that can be carried out various mining activities, including excavation mining C. Pati Regency Government includes mining mining area in Spatial Plan (RTRW) as regulated in Regional Regulation No 5 Year 2011. For several years the last area of the mining allotment, especially the excavation of C, precisely raises the elements who wildly prioritize personal interests. They conducted excavations in areas that are suitable for their purposes, such as in Gembong, Gunungwungkal, Tayu, Sukolilo, Kayen, Tambakromo, and several other districts.As a result, massive environmental destruction occurred. The mining is not licensed for the excavation of C minerals, so that taxes and levies are not paid and the transport of the excavated products using transport vehicles passing through public facilities, ie, highways that interfere withother road users. The illegal mining of C illegally brings bad impacts, especially for the environment, so that how to solve and handling illegal mining cases of C without permit (Illegal) in South Kendeng Mountain Area and North Kendeng Mountains in Pati Regency is done. The handling of illegal mining of C mining in Kendeng Selatan and Kendeng Utara mountains in Pati Regency is done both penal and non penal.Key Words: Case Handling, Illegal mining C Client, Pati Regency